Effect of thermosonication on pectin methylesterase activity and quality characteristics of orange juice - Lorencini Schuina, Guilherme (Revista Ciência Agronômica, 2021)
Pectin methylesterase (PME) is the enzyme responsible for quality losses in orange juice and pasteurizationis used to inactivate PME. This process decreases the sensory and nutritional aspects of the beverage. This study aimed toevaluate the effect of combined ultrasound and moderate temperature on several quality parameters of orange juice, andwhether the used treatment resulted in a reduction of PME activity when compared to thermally treated samples and naturaljuice. Thermosonication is an alternative preservation method that allows a signifi cant decrease in PME activity and a smallerloss of vitamin C. The treatment with 40 kHz ultrasound and a temperature of 60 °C resulted in the highest reduction of PMEactivity. For ascorbic acid, the lower the heat used in combination with sonication, the smaller the loss of this compound.Soluble solids content, pH, and color of the juice did not alter during processing.